Potential Of Fermented Traditional Food As A Gastronomic Tourism Attraction In Mengwi District, Badung Regency, Bali - Tri Sutaguna, I Nyoman; Dwi Setiawan, Ida Bagus (Journal of Management, 2024)
One of the objectives of tourism development in the territory of Indonesia is traditional cuisine, especially Balinese cuisine. On the other hand, traditional food has not grown according to the expected plan. This is because local food in rural areas that have abundant natural culinary abilities have not been developed. For example, fermented food products can be replaced with delicious dishes and made from flour dough (biang) in Mengwi District. The purpose of this in-depth research is to recognize the gastronomic significance of traditional fermented food in Mengwi District, Mengwi District, Badung Regency, and what steps can be tried to make it a tourist attraction. Observation, in-depth interviews, and documentation studies are information collection techniques used in this research, which uses qualitative research methods and several planned informants are selected. Gastronomy theory, tourism theory, cultural theory, and some microforms are theories that are used as the basis for research. As a finding from the results of the research to make it a famous tourist attraction, flour dough (biang) which is a type of fermented food needs to be socialized and its production increased. Preparation of ingredients, processing, variations, good quality products that can be enjoyed by consumers and tourists, and how to serve the food are part of the effort to improve the gastronomy of traditional fermented foods. Not only that, dough made from fermented flour provides economic, social, and aesthetic significance to this food item. Processing quality products that can be enjoyed by consumers and tourists, as well as serving food are part of the effort to improve the ability to cook traditional fermented foods.